İş Süreçlerinin Yeniden Yapılandırılması Ve Bir Uygulama - Bilir, Canser (Sosyal Bilimler Enstitüsü, 2001)
Literatürde 1990'lı yılların başında rastladığımız "Yeniden Yapılandırma (Reengineering)", dünyada ve Türkiye'de şirketlerin artan rekabet ortamına uyum sağlamak ve yeni bir yönetim anlayışının yerleştirilmesi amacıyla başvurdukları önemli bir yaklaşım olmuştur. Tanım ve Anahtar Kavramlar İş Süreçlerinin Yeniden Yapılandırılması (İSYY) bir kurumun katma değer üreten stratejik süreçlerinin, sistem, politika ve organizasyon yapılannın süreçleri destekleyip, iş akışlan ve organizasyon verimliliğini optimize edecek şekilde hızlı ve radikal bir şekilde yeniden tasarlanmastdır. İSYY tüm süreçleri hedeflemez, sadece stratejik ve katma değer üreten süreçleri hedefler. Stratejik süreç şirket varlığının merkezinde yer alan süreçtir. Amaçlann, hedeflerin ve stratejinin başarılması için temel araçtır. Çoğu durumda bir şirketin stratejik ve katma değer üreten süreçlerinin sayısı yarım düzineyi geçmemektedir. İş Süreçleri destekleyici bir altyapı ile daha verimli hale gelmektedir. Bu altyapının tüm elemanları yeniden tasarlanmış süreçler ile uyumlu hale getirilmelidir, örneğin, veri işleme sistemleri yeni sürecin ihtiyaçları ile uyumlu olacak şekilde revize edilmelidir. Politikalar ve organizasyonel yapılar da aynı şekilde yeni süreci destekleyecek şekilde yeniden tasarlanmalıdır. İSYY çalışması bir yandan karlılığın, pazar payının, gelir ve yatınmın geri dönüşü (ROI) oranının artırılmasını, diğer yandan da varlık artışı ve maliyetlerde azalmayı hedeflemektedir. Yeniden Yapılandırma Metodolojisi 1. Aşama: Yeniden Yapılandırmaya Giriş: Üst yönetim projeyi başlatır. Halihazırdaki durum ve çalışmaya neden gereksinim duyulduğu açık şekilde ortaya konur. Bir vizyon belirlenerek tüm çalışanlara duyurulur. 2. Aşama İşletme Süreçlerinin Belirlenmesi: İşletme içi ve dışıyla ilgili tüm süreçler, birbirleriyle ilişkileri de göz önüne alınarak geniş bir perspektifle incelenir. Tüm süreçlerin süreç haritası yardımıyla grafikle gösterilmesi faydalıdır. 3. Aşama: İşletme Süreçlerinin Seçilmesi: Bu aşamada yeniden tasarlanacak süreç seçilmeye çalışılır. Buradaki en önemli kriter, müşterilere yönelik olarak en fazla iyileştirmenin sağlanacağı sürecin seçitmesidir. xı 4. Aşama Seçilen Süreçlerin Anlaşılması: Süreçlerin şimdiki durumlan ve gelecekte olması beklenen durumlan üzerinde yoğunlaşılır. Detaylı bir analiz yapmaktan kaçınılır. 5. Aşama: Seçilen Süreçlerin Yeniden Tasarlanması: En yaratıcı olan aşamadır. Bu aşama hayal gücünün kimi zaman çılgınca bile sayılabilecek şekilde kullanılmasını gerektirir. 6. Aşama: Yeniden Tasarlanan Süreçlerin Uygulanması: Son aşama, tüm bu aşamalar sonunda ortaya çıkan yeni süreçlerin uygulanmasıdır. Önceki 5 aşama başarılı olursa, uygulamada bir sorunla karşılaşılmayacaktır Yeniden Yapılandırma İlkeleri Yeniden yapılandırma çalışması sırasında uyulması gereken önemli yeniden yapılandırma ilkeleri şöyle sıralanabilir; * Müşteriler üzerinde odaklanılır ve müşteriler için daha yüksek değer üretilir. * Tek temas noktasını müşteriye karşı sürecin gerçekleştirilmesinden sorumlu olan vaka yöneticisi oluşturur. * Yaratıcı bir çalışma ortamı oluşturularak öğrenme ve gelişmenin teşvik edilir. * Sürecin adımlan çizgisellikten kurtarılarak doğal sırasıyla gerçekleştirilir. * Süreçlerin değişik taleplere cevap vermek üzere pek çok versiyonu vardır. * Katma değer üretmeyen kontrol ve denetimler azaltılır, genel ve geciktirilmiş kontroller tercih edilir. * Girdiler yerine çıktılar üzerinde yoğunlaşılır ve performans kriterleri ile teşviklerle müşteriyle ilişkili sonuçlar arasında bağlantı sağlanır. » Yönetimin kontrolünün korunması yerine değer üretilmesine öncelik verilir. » Ağ sistemlerinin insanlar ve faaliyetler arasında kullanılır. * Tüm organizasyonda çalışma ekipleri ve vaka yöneticileri kullanılır. * Sorumluluklann organizasyon, tedarikçi ve müşteriler arasında yeniden paylaştırılır. * İlgi ve katılımı teşvik edilir. * İşin gerçekleştirilmesi ile ilgili kararlan işi yapan elemanlar verir. * İşlerin basit görevlerden çok boyutlu işler haline getirilir * Temel süreçlerinin sayısının az tutulur ve bunlann hepsinin dış müşteri ile ilişkili olması sağlanır. * Geri besleme kanallannın oluşturulur. Bu prensipler uygulanarak şu sonuçlar elde edilebilecektir; s Azalan bürokrasi ve işgücü maliyetleri, * İş tekrarları ve hatlann azalması, xii S Artan karlılık, V Yetkilendirilmiş ve motive edilmiş çalışanlar. En yaygın yeniden yapılandırma hataları Orta kademe yöneticilerin katılımının sağlanamaması Süreç yerine fonksiyon üzerine odaklanmak Temel süreçler yerine alt süreçlerin yeniden yapılandırılmasına çalışmak Süreci değiştirmek yerine sabit kalmasına çalışmak Küçük çaplı geliştirmelerle tatmin olmak Yeniden yapılandırmayı aşağıdan yukarıya uygulamaya çalışmak

Reengineering, which we have met at the beginning of 1990's in literature, has been very important approach for the companies both in the world and Türkiye for adopting themselves to increasing competition and establishing a new management understanding. Definition and Keywords Reengineering is the rapid and radical redesign of strategic, value added business processes - systems, policies and organizational structures that support them to optimize the work flows and productivity in an organization. A process is an interrelated series of activities that converts business inputs into business outputs. For example, "fulfill orders" is a process. Processes themselves are composed of activities. Within the "fulfill orders" process, an activity might be "check credit" or "pack order." There are really just three primary types of activities in a business process: value-adding activities, hand-off activities and control activities. Value-adding activities add something of importance to the customer-a product or service that a customer needs, wants and is willing to pay for. Hand-off activities are those everyday transactions that move pieces of work across functional and departmental boundaries within the company. Control activities are there to control the hand-offs across the boundaries. Not all processes are targets for reengineering. Reengineering only targets those that are strategic and value-added. Strategic processes are the ones central to the company's definition of itself. They are its essential vehicle for achieving objectives, goals, positioning and stated strategy. The primary targets of business process reengineering, then, are processes that are both strategic and value-added. Most business units can be functionally decomposed into a dozen or so processes. In most cases, no more than a half- dozen processes are both strategic and value-added. To achieve maximum return on your investment in reengineering, it is both logical and prudent to begin by focusing on the most important processes in the corporation. They are facilitated by a support infrastructure. Each of the infrastructure items must be aligned with newly reengineered process flows. For example, data processing systems must be revised to ensure availability of data consistent with new process needs. Policies must be revised so that reports mandated only under the old process do not continue to be produced. Organizational structures supporting the work must be realigned so that, for example, the process itself has an owner, instead of having its ownership shared by several function managers. A business XIV process cannot be changed unless aH of these supporting elements are changed as well. Reengineering Metodology Stage 1: Introduction into Business Reengineering The CEO initiates the project. He describes briefly and pragmatically the current business situation to start actions. He introduces her vision to the employees of the company. Stage 2: Identification of Business Processes This step looks at the broad picture, of how processes interact within the company and in relation to the outside world. One deliverable is a graphical display of all processes Stage 3: Selection of Business Processes The third step serves to select such processes, which - once reengineered - will lead to high value for the company's customers. Also processes, that lend themselves to easy reengineering are being selected. Stage 4: Understanding the Selected Business Processes This step does not dwell on a detailed analysis of the functioning of the selected business processes, rather concentrates on the performance of the current processes as opposed to what is expected from them in the future. Stage 5: Redesign of the Selected Business Processes The fifth step is the most creative of all. It is characterized by imagination, lateral thinking and some sort of craziness Stage 6: Implementation of Redesigned Business Processes The last step covers the implementation phase of the Business Reengineering project. Success of the implementation, once the five preliminary steps have been properly performed. The Principles of Business Reengineering The principles of Business Reengineering emerged during the early 1990's. Here are some important reengineering principles; * Externally, focus on end customers and the generation of greater value for customers. * Give customers and users a single and accessible point of contact * Internally, focus on harnessing more of the potential of people and applying it to those activities which identify and deliver value to customers. * Encourage learning and development by building creative working environments. * Think and execute as much activity as possible horizontally, concentrating on flows and processes (including communication) through the organization. XV * Remove non-vaîue added activities, undertake parallel activities, speed up response and development times. * Concentrate on outputs rather than inputs, and link performance measures and rewards to customer related outputs. * Give priority to the delivery of value rather than the maintenance of management control. » Network related people and activities. Virtual corporations are becoming commonplace in some business sectors. * Implement work teams and case managers extensively throughout the organization. * Move discretion and authority closer to the customer, and re-allocate responsibilities between the organization, its suppliers and customers. * Encourage involvement and participation. This requires error-tolerant leadership. * Ensure people are equipped, motivated and empowered to do what is expected of them. * Where ever possible, people should assume full responsibility for managing and controlling themselves. * Work should be broadened without sacrificing depth of expertise in strategic areas. * Avoid over-sophistication. Don't replace creative thinking with software tools. * Keep the number of core processes to a minimum (approx. 12). They all should be directed to external customers. * Build learning, renewal, and short feedback loops into business processes. * Ensure that continuous improvement is built into implemented solutions. The application of these principles causes the following benefits.S Reduced bureaucracy and overhead costs, S Avoid redundancy, rework and mistakes, s increased profits, v Empowered and motivated workers Common causes of reengineering failure Lacking active participation by senior management. Attempting to reengineer a function istead of a process. Reengineering subprocesses instead of major business processes. Trying to fix a process instead of changing it. Settling for minor improvements. Attenpting to reengineer from bottom up.
Business Process Reengineering And Au Implementation
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2001
Thesis (M.A.) -- İstanbul Technical University, Institute of Social Sciences, 2001
Keywords: İşletme; Süreç yönetimi; Yeniden yapılanma; İş süreçleri; Business Administration; Process management; Restructuring; Business processes